Cooperative Power Scheduling for a Network of MIMO Links - Dong, X.; Rong, Yue; Hua, Y. (IEEE, 2010)
A cooperative power scheduling algorithm developed by Wang, Krunz and Cui is extended for an ad hocnetwork of MIMO links. This algorithm, referred to as pricebased iterative water filling (PIWF) algorithm, is a distributed algorithm by which each link computes its power scheduling through an iterative and cooperative process. The cooperation among all links is achieved by adaptive price factors appliedby each link. Compared to a centralized power scheduling algorithm, the PIWF algorithm is much more efficient in computation although not as efficient in network throughput. Compared to a non-cooperative counter-part by Demirkol and Ingram where all price factors are zero, the PIWF algorithm requires additional in-network computation but is more efficient in network throughput.